PENERAPAN MODEL PEMBELAJARAN AUDITORY, INTELLECTUALLY, REPETITION (AIR) UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Rahmatul Hayati; Mirunnisa Mirunnisa; Junaidi Junaidi (Jurnal Real Riset, 2022)
Increasing students' mathematical representation skills is one of the factors in achieving the goals of mathematics education. Applying the Auditory, Intellectually, Repetition (AIR) learning model is a learning process in which the goals and desires of individuals or students are built and achieved openly on the material of a two-variable linear equation system (SPLDV). The AIR learning model is a learning model in which it has three main phases, namely auditory (listening), intellectually (understanding), repetition (repetition). The formulation of the problem in this study is whether there is a difference in the average application of the Auditory, Intellectually, Repetition (AIR) learning model on students' mathematical representation abilities with the application of conventional learning models. The population in this study is class X semester 1 of SMA Negeri 2 Sigli in 2021/2022. The sampling technique used purposive sampling technique. This study used two classes, namely the experimental class and the control class. Learning in class X MIPA-2 as many as 20 students as an experimental class was carried out using the AIR learning model, while learning in class X Language-1 as many as 16 students as a control class was carried out using conventional learning models. The research instrument is in the form of questions given in the form of pretest and posttest consisting of five essay questions. Based on the results of data processing with the help of statistical software, the results of the normality test on the pre-test with sig. 0.20 0.05 and post-test with sig. 0.20 0.05. By using the t-test, namely the Independent Sample T-test in the post-test with a significance level of 5%, the significance value of 0.028 0.05 is obtained, then H0 is rejected and H1 is accepted. So it can be concluded that there is a significant difference in the application of the Auditory, Intellectually, Repetition (AIR) learning model to students' mathematical representation abilities between the experimental class and the control class. Thus, the AIR learning model can be used as an alternative model in mathematics learning to improve students' mathematical representation skills.Keywords : Application of Model, (AIR) Auditory, Intellectually, Repetition, Students' Mathematical Representation Ability